Implementasi PSAK 109 pada Pengelolaan Zakat, Infak dan Sedekah di BAZNAS Kabupaten Cilacap - Purnamasari, Riski; Munawarah, Munawarah (Multidisciplinary Journal of Education , Economic and Culture, 2024)
This research is motivated by an incident involving the ZIS management institution which is responsible for managing financial reports in the context of zakat management, which has not been able to ensure that its financial reporting is in accordance with PSAK 109 regulations. The lack of trust of muzaki (people who pay zakat) in zakat management institutions can hinder the proper zakat management process. distributed to mustahik (zakat recipients) effectively. The aim of this research is to analyze the application of PSAK 109 ZIS in zakat management at BAZNAS Cilacap Regency. This research uses a qualitative approach with a descriptive type. Data collection techniques in this research used several methods of observation, interviews and documentation. The research results show that the preparation of financial reports for zakat, infaq/alms funds at BAZNAS Cilacap Regency has been presented in the form of a fund management report in accordance with PSAK 109 guidelines